Nucleotide sequencing and characterization of Pseudomonas putida catR: a positive regulator of the catBC operon is a member of the LysR family. - Rothmel, R K (1990)
Pseudomonas putida utilizes the catBC operon for growth on benzoate as a sole carbon source. This operon is positively regulated by the CatR protein, which is encoded from a gene divergently oriented from the catBC operon. The catR gene encodes a 32.2-kilodalton polypeptide that binds to the catBC promoter region in the presence or absence of the inducer cis-cis-muconate, as shown by gel retardation studies. However, the inducer is required for transcriptional activation of the catBC operon. The catR promoter has been localized to a 385-base-pair fragment by using the broad-host-range promoter-probe vector pKT240. This fragment also contains the catBC promoter whose -35 site is separated by only 36 nucleotides from the predicted CatR translational start. Dot blot analysis suggests that CatR binding to this dual promoter-control region, in addition to inducing the catBC operon, may also regulate its own expression. Data from a computer homology search using the predicted amino acid sequence of CatR, deduced from the DNA sequence, showed CatR to be a member of a large class of procaryotic regulatory proteins designated the LysR family. Striking homology was seen between CatR and a putative regulatory protein, TfdS.